NRF2/Itaconate Axis Regulates Metabolism and Inflammatory Properties of T Cells in Children with JIA - Anandhi Rajendiran; Sudheendra Hebbar Subramanyam; Patricia Klemm; Vera Jankowski; Jorg van Loosdregt; Bas Vastert; Kristina Vollbach; Norbert Wagner; Klaus Tenbrock; Kim Ohl (MDPI AG, 2022)
Background: CD4+ T cells critically contribute to the initiation and perturbation of inflammation. When CD4+ T cells enter inflamed tissues, they adapt to hypoxia and oxidative stress conditions, and to a reduction in nutrients. We aimed to investigate how this distinct environment regulates T cell responses within the inflamed joints of patients with childhood rheumatism (JIA) by analyzing the behavior of NRF2-the key regulator of the anti-oxidative stress response-and its signaling pathways. Methods: Flow cytometry and quantitative RT-PCR were used to perform metabolic profiling of T cells and to measure the production of inflammatory cytokines. Loss of function analyses were carried out by means of siRNA transfection experiments. NRF2 activation was induced by treatment with 4-octyl-Itaconate (4-OI). Results: Flow cytometry analyses revealed a high metabolic status in CD4+ T cells taken from synovial fluid (SF) with greater mitochondrial mass, and increased glucose and fatty acid uptake. This resulted in a heightened oxidative status of SF CD4+ T cells. Despite raised ROS levels, expression of NRF2 and its target gene NQO1 were lower in CD4+ T cells from SF than in those from blood. Indeed, NRF2 activation of CD4+ T cells downregulated oxidative stress markers, altered the metabolic phenotype and reduced secretion of IFN-γ. Conclusion: NRF2 could be a potential regulator in CD4+ T cells during chronic inflammation and could instigate a drift toward disease progression or regression, depending on the inflammatory environment.